Cirque du freak : lord of the shadows - Shan, Darren (New York : Little, Brown, 2005)
When Darren Shan returns home, he is met by old enemies and scores to be settled, and with destiny certain to destroy him, the world seems doomed to fall to the Ruler of the Night.
790
Accelerated Reader AR
Keywords: Vampires -- Juvenile fiction; Horror fiction